Optimization of propolis extraction with natural deep eutectic solvents using central composite design - Alpat, Ufuk; Nar, Tarik; Karasu, Salih; Sagdic, Osman (ELSEVIER, 2023)
This study examines the potential of using natural deep eutectic solvents (NADESs) to extract phenolic compounds from propolis and optimizes the extraction process using central composite design (CCD). Different mixtures of NADESs were prepared and analyzed for stability, physicochemical properties, and ability to dissolve phenolic compounds, and four NADES, namely NADES 62 (Betaine, Malic acid and proline 1:1:1, water 15% w/ w, NADES 57 (Choline Chloride, Xylitol, Malic Acid 1:1:1, water 15% w/w), NADES 58 (Betaine, Malic acid and proline 1:1, water 15% w/w), NADES 76 (Proline, Citric Acid 2:1 water 15%) were evaluated for the extraction process. The full quadratic model showed that the linear effect of time, temperature, and ultrasound amplitude was found to be significant on the models for NADESs and 80% Ethanol. NADES 62 showed highest extraction yield and the optimal extraction conditions were 80 degrees C, 135 min, and 100% amplitude. The highest total phenolic and total flavonoid content for NADESs achieved was 5284.2 mg GAE/L and 1531.2 mg QE/L, respectively. With the optimization carried out, the phenolic profile and antimicrobial activity analyses were conducted, has reinforced the information that NADESs can be a good alternative to conventional solvents for propolis extraction.
Keywords: Natural Deep Eutectic Solvents; Propolis Extraction; Optimization; Central Composite Design; BIOACTIVE COMPOUNDS; TURKISH PROPOLIS; IONIC LIQUIDS; ANTIOXIDANT; BEHAVIOR; Plant Sciences; Pharmacology & Pharmacy